Economic emission dispatch for wind–fossil‐fuel‐based power system using chemical reaction optimisation. (4th December 2014) - Roy, Provas Kumar; Hazra, Sunanda
Summary: This paper presents a chemical reaction optimisation algorithm based on the chemical molecular reaction to optimise total cost in wind–fossil‐fuel‐based power systems, while all operating constraints are satisfied. With the continuing search for alternatives to conventional energy sources and global warming, it is necessary to include wind energy conversion system generators in the economic load dispatch problem. The random nature of wind power is modelled using Weibull probability distribution function. Because of uncertainty in wind power, wind cost is generalised by including overestimation and underestimation cost of available wind power. The proposed approach is examined and tested on the standard Institute of Electrical and Electronics Engineers 30‐bus test system having three conventional thermal generators, two gas generators, one oil generator and two wind turbines and a 40‐unit test system having three wind turbines and 37 thermal generating units. The simulation results show that the proposed algorithm gives comparatively better operational cost compared with other optimisation techniques. Copyright © 2014 John Wiley & Sons, Ltd.